PENEGAKAN HUKUM OLEH KEPOLISIAN TERHADAP AKSI UNJUK RASA BERSIFAT ANARKIS DIWILAYAH HUKUM POLRES SIAK - S, Zulkarnain; Setiawan, Reski Egi; Shaleh, Ali Ismail (JURNAL DARMA AGUNG, 2022)
Demonstrations are a forum for the Indonesian people to express their aspirations in public, none other than this is aimed at achieving something that will bring change in the future, of course this effort is carried out by the police so as not to cause unwanted things, during demonstration activities in Siak Regency of course there are some that don't go smoothly where demonstrations are accompanied by road blockades, vandalism and uncooperative actions as well as other actions that can harm other people from the demonstration participants resulting in demonstrations categorized as anarchist, of course this violates the norms - existing norms and rules and of course can refer to crime, the police, especially the Siak resort police as the party that carries out security for individuals who cause unconducive situations in which the perpetrator takes persuasive actions so that he can influence other people to make efforts to destroy, The types of criminal acts that stand out are sedition and vandalism.